2011
DOI: 10.1519/jsc.0b013e3181db9f41
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Static and Dynamic Stretching on Hip Dynamic Range of Motion During Instep Kicking in Professional Soccer Players

Abstract: The purpose of this study was to examine the effects of static and dynamic stretching within a pre-exercise warm-up on hip dynamic range of motion (DROM) during instep kicking in professional soccer players. The kicking motions of dominant legs were captured from 18 professional adult male soccer players (height: 180.38 ± 7.34 cm; mass: 69.77 ± 9.73 kg; age: 19.22 ± 1.83 years) using 4 3-dimensional digital video cameras at 50 Hz. Hip DROM at backward, forward, and follow-through phases (instep kick phases) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 30 publications
0
52
0
3
Order By: Relevance
“…On the other hand, SS has also been shown to provide ROM increases similar to those of PNF within a single session (Condon and Hutton 1987;Maddigan et al 2012). There is also conflict in the DS literature, with some studies reporting that an acute bout of DS provides either similar (Beedle and Mann 2007;Perrier et al 2011) or greater (Duncan and Woodfield 2006;Amiri-Khorasani et al 2011) increases in flexibility than does SS, whereas many other studies have reported that DS was not as effective as SS within a single preactivity routine (Samuel et al 2008;Bacurau et al 2009;Sekir et al 2010;Barroso et al 2012;Paradisis et al 2014). Few studies have compared PNF with DS; however, Wallin and colleagues (1985) showed greater ROM increases after PNF (11%-24%) than after ballistic stretching (3%-7%) over 14 training sessions.…”
Section: Acute Effects Of Ss Ds and Pnf On Joint Rommentioning
confidence: 99%
“…On the other hand, SS has also been shown to provide ROM increases similar to those of PNF within a single session (Condon and Hutton 1987;Maddigan et al 2012). There is also conflict in the DS literature, with some studies reporting that an acute bout of DS provides either similar (Beedle and Mann 2007;Perrier et al 2011) or greater (Duncan and Woodfield 2006;Amiri-Khorasani et al 2011) increases in flexibility than does SS, whereas many other studies have reported that DS was not as effective as SS within a single preactivity routine (Samuel et al 2008;Bacurau et al 2009;Sekir et al 2010;Barroso et al 2012;Paradisis et al 2014). Few studies have compared PNF with DS; however, Wallin and colleagues (1985) showed greater ROM increases after PNF (11%-24%) than after ballistic stretching (3%-7%) over 14 training sessions.…”
Section: Acute Effects Of Ss Ds and Pnf On Joint Rommentioning
confidence: 99%
“…Reduction of peak torque parameters and variables of strength and power after PNF stretching may be incurred as a result of muscle fatigue induced in the active phase hold -relax procedure [16]. Based on these results of their research, Khorasani and Kellis [17] suggested that dynamic stretching is probably more effective in increasing quadriceps muscle activity and knee extension angular velocity. These results suggest that dynamic stretching is ideal for warm up in order to achieve maximum force performance of knee extensors and flexors.…”
Section: Discussionmentioning
confidence: 96%
“…Com relação aos exercícios de alongamento dinâmico, corroboramos também com os resultados de investigações que atestaram efeitos benéficos no desempenho de diferentes métodos para avaliar a força e a potência de jogadores de futebol, submetidos a este método, como na velocidade em sprints (LITTLE; WILLIAMS, 2006;GELEN, 2010;RODRÍGUEZ;ANDÚJAR, 2010;ALIKHAJEH et al, 2011), potência no chute (GELEN, 2010;AMIRI-KHORASANI et al, 2011) e agilidade (MCMILLIAN et al, 2006;AMIRI-KHORASANI et al, 2010 (MAREK et al, 2005;SIATRAS et al, 2008;GREGO NETO;MANFFRA, 2009), parece que o alongamento dinâmico pode promover aumento no desempenho muscular tanto em volumes maiores (MCMILLIAN et al, 2006;AMIRI-KHORASANI et al, 2011;VAN GELDER;BARTZ, 2011) quanto nas séries de 10 repetições, propostas no presente estudo, questionando assim, a necessidade da prescrição de séries de alongamento dinâmico superiores a esta, nas rotinas de aquecimento de jogadores de futebol profissional.…”
Section: Discussionunclassified